2000
DOI: 10.1016/s0005-2736(00)00218-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the third helix of Antennapedia homeodomain and a phospholipid monolayer, studied by ellipsometry and PM-IRRAS at the air–water interface

Abstract: The penetratin peptide, a 16 amino acid sequence extracted from Antennapedia homeodomain, is able to translocate across a neural cell membrane through an unknown mechanism, most likely a non-specific interaction with membrane lipids. Beyond its potential application as vector targeting small hydrophilic molecules and enabling them to reach a cell nucleus, this observation raises intriguing questions concerning the physico-chemistry of peptide-lipid interactions. Here we present a study of the role of lipid sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 18 publications
7
78
0
Order By: Relevance
“…The independence of binding to a saturable receptor agrees with the lack of cell specificity and suggests that the peptide interacts directly with fosfolipids as has been described for another transport peptide (30). Because the hemolytic activity correlated to some extent with translocation activity, the influence was tested for membrane potential on hemolysis of human red blood cells.…”
Section: Discussionsupporting
confidence: 63%
“…The independence of binding to a saturable receptor agrees with the lack of cell specificity and suggests that the peptide interacts directly with fosfolipids as has been described for another transport peptide (30). Because the hemolytic activity correlated to some extent with translocation activity, the influence was tested for membrane potential on hemolysis of human red blood cells.…”
Section: Discussionsupporting
confidence: 63%
“…These contacts draw the PTDs in close to the plasma membrane, where, by an unknown mechanism, a rapid nonendocytic process occurs, which delivers the PTDs and their cargoes into the cell. This second step may be mediated by interactions of charged heads of phospholipids groups with the cationic residues of the PTDs, as suggested by studies from the Antennapedia PTD (18,29,(31)(32)(33)(34)(35)(36)(37). These data are supported by the fact that longer PTDs (10-and 12-mers) are better able to mediate transduction in GAG-deficient lines than short PTDs (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Internalization of Antennapedia, TAT, and arginine homopolymers has been shown to be nonsaturable and achiral, and it is not reliant on particular secondary structural elements within the PTD, as evidenced by mutagenesis experiments, use of retro-inverso peptides, ␤-peptides, peptoids, and substitution with D-enantiomers of PTD residues (19, 21, 26 -30). The broad range of transducible cell targets points toward the involvement of ubiquitously shared cellular structures, such as plasma membrane phospholipids (18,29,(31)(32)(33)(34)(35)(36)(37). Data have supported the role of heparan sulfate proteoglycans as a surface binding target for the TAT protein (38 -40), although more recent work has suggested that they are not required for internalization of the TAT PTD (23,41,42).…”
mentioning
confidence: 99%
“…Following fluorescently labeled Antennapedia peptide by microscopy suggested that only peptide interaction with membrane lipids is required and no pore formation occurs (14). Many studies have shown that electrostatic interactions of TAT and other PTDs with the negative charges of the membrane are important for transduction (9,(15)(16)(17). Even though TAT interacts with negatively charged membrane phospholipids (18), 2 it has also been shown that TAT has a higher affinity for negatively charged membrane sugars, such as glycosaminoglycans (18).…”
mentioning
confidence: 99%